Xenology and xenotopography of Bernhard Waldenfels - Maj, Krzysztof M. (Hybris, 2014)
The paper strives to adapt Bernhard Waldenfels’ xenology and so called ‘xenotopography’ for the philosophico-literary studies in fantastic world-building with a special concern of the ‘portal-quest’ model of fantasy and SF. Following Waldenfel’s remarks on the nature of post-Husserlian diastasis of our world [Heimwelt] and otherworld [Fremdwelt] and acknowledging the consequences of allocating one’s attitude towards the otherness in the symbolical borderland [‘sphere of intermonde’] in between, it is examined whether such a model can occur in the fantastic literature and what may be the consequence of xenotopographic reconsideration of its basic ontological premises. Additionally, the article offers an original xenotopograpfic model of world-building which addresses three carefully chosen case studies of fantastic worlds from Orson Scott Card’s Ender’s Game tetralogy, Neil Gaiman’s Stardust and George R. R. Martin’s The Song of Ice and Fire. In the end, it is suggested that hitherto presented xenotopography gravely inspired a postmodern shift in the genres of fantasy and SF which results in more ethically conscious representations of the otherness and even more concise and alien comprehensive world-building.